Psychosocial Predictors of Islamic Education Teachers’ Interest in Implementing Deep Learning: An Application of Social Cognitive Career Theory - Abdul Hakim; Amirudin; Abdul Kosim; Mohd. Sobri Bin Ellias (Cendekia: Kependidikan dan Kemasyarakatan, 2026)
Implementing deep learning in Islamic education requires teachers who are willing to adopt innovative pedagogical approaches. This study examines the relationships among self-efficacy, outcome expectations, environmental support, and Islamic Education teachers’ interest in implementing deep learning, based on Social Cognitive Career Theory (SCCT). A quantitative cross-sectional study was conducted on 29 Islamic Religious Education (IRE) teachers from Madrasah Aliyah in Ponorogo Regency, Indonesia, using purposive sampling. Data were collected through an online questionnaire and analyzed using descriptive statistics and univariable binary logistic regression. The results showed that self-efficacy (OR = 0,100; 95% CI: 0,018-0,556; p = 0,009), outcome expectations (OR = 0,030; 95% CI: 0,003–0,308; p = 0,003), and environmental support (OR = 0,148; 95% CI: 0,029–0,759; p = 0,022) were significantly related to teachers’ interest in implementing deep learning. Teachers with positive self-efficacy, positive outcome expectancy, and high environmental support were more likely to be interested in implementing deep learning. These findings highlight the importance of strengthening teachers’ psychosocial resources to support educational innovation in Madrasah Aliyah.